2018
DOI: 10.5194/acp-18-14851-2018
|View full text |Cite
|
Sign up to set email alerts
|

Seasonal evaluation of tropospheric CO<sub>2</sub> over the Asia-Pacific region observed by the CONTRAIL commercial airliner measurements

Abstract: Abstract. Measurement of atmospheric carbon dioxide (CO2) is indispensable for top-down estimation of surface CO2 sources/sinks by an atmospheric transport model. Despite the growing importance of Asia in the global carbon budget, the region has only been sparsely monitored for atmospheric CO2 and our understanding of atmospheric CO2 variations in the region (and thereby that of the regional carbon budget) is still limited. In this study, we present climatological CO2 distributions over the Asia-Pacific region… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
18
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2
1

Relationship

2
7

Authors

Journals

citations
Cited by 23 publications
(19 citation statements)
references
References 63 publications
(90 reference statements)
1
18
0
Order By: Relevance
“…While the observed gradient is similar to previously reported studies (e.g. Wofsy, 2011;Sweeney et al, 2015;Umezawa et al, 2018), measurements from CoMet 1.0 also clearly indicate the increase in atmospheric concentrations over the past years. For example, the CH 4 mixing ratios measured during the IMECC campaign in autumn 2009 (Geibel et al, 2012) were approximately 60 ppb lower throughout the atmospheric column than those observed in 2018.…”
Section: Vertical Structure Of the Atmospheresupporting
confidence: 91%
“…While the observed gradient is similar to previously reported studies (e.g. Wofsy, 2011;Sweeney et al, 2015;Umezawa et al, 2018), measurements from CoMet 1.0 also clearly indicate the increase in atmospheric concentrations over the past years. For example, the CH 4 mixing ratios measured during the IMECC campaign in autumn 2009 (Geibel et al, 2012) were approximately 60 ppb lower throughout the atmospheric column than those observed in 2018.…”
Section: Vertical Structure Of the Atmospheresupporting
confidence: 91%
“…However, unlike the clean‐air environment in Alaska where previous studies have been performed (Commane et al, 2017; Jeong et al, 2018), Korea is located at the center of the East Asia region where a rapid increase in anthropogenic carbon emissions have been reported over the recent decades (Global Carbon Project, 2018). The higher increasing trends of CO2YellowSea and CO2land than that of the globally averaged CO 2 concentration (2.07 ppm/year), derived from the NOAA/ESRL data ( Dlugokencky & Tans, 2019), indicate that the influences of anthropogenic emissions on the spatiotemporal variations in CO 2 concentrations cannot be negligible over the region as highlighted in previous modelling (Ballav et al, 2012, 2016) and observation studies (Umezawa et al, 2018).…”
Section: Discussionmentioning
confidence: 82%
“…The seasonal cycle patterns in the NH often show a maximum in spring and a minimum in summer, but CO increases around October-November were considerably smaller in the NH than the SH. It is suggested that the seasonal CO signals due to Indonesian fire emissions were significantly masked by continental outflows of larger anthropogenic emissions from the East Asia region to the western North Pacific (e.g., Umezawa et al 2018). ln order to further investigate the Indonesian fire emissions, we focus on the CO seasonal cycles in the SH.…”
Section: Interannual Variation Of Upper Tropospheric Co Over the Westmentioning
confidence: 99%
“…This result strongly suggests that climate-CO relationship may be different between 1997 and other years. Climate can influence atmospheric CO via process-based emission impacts both near and distant to Indonesia, combined with impacts on transport and photochemistry (e.g., Rowlinson et al 2019).…”
Section: Link Between Co and Climatementioning
confidence: 99%